Infections in the Developing Brain: The Role of the Neuro-Immune Axis - Kim, John; Erice, Clara; Rohlwink, Ursula K.; Tucker, Elizabeth W. (Frontiers in Neurology, 2022)
Central nervous system (CNS) infections occur more commonly in young children than in adults and pose unique challenges in the developing brain. This review builds on the distinct vulnerabilities in children’s peripheral immune system (outlined in part 1 of this review series) and focuses on how the developing brain responds once a CNS infection occurs. Although the protective blood-brain barrier (BBB) matures early, pathogens enter the CNS and initiate a localized innate immune response with release of cytokines and chemokines to recruit peripheral immune cells that contribute to the inflammatory cascade. This immune response is initiated by the resident brain cells, microglia and astrocytes, which are not only integral to fighting the infection but also have important roles during normal brain development. Additionally, cytokines and other immune mediators like matrix metalloproteinases, not only play a role in BBB permeability and peripheral cell recruitment, but also in brain maturation. Release of cytokines and activation of microglia and astrocytes during infection combine to adversely affect normal neurodevelopment. Perturbations to normal brain development manifest as neurodevelopmental and neurocognitive impairments common among children who survive CNS infections and are often permanent. In this part 2 of the review series, we broadly summarize the unique challenges CNS infections create in a developing brain and highlight current knowledge gaps.